Integrating Life Skills in Handball Training Programs for Positive Youth Development - Prabowo, Indra; Subhakti Prawira Raharja, Didik; Sofyan, Davi (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to investigate the impact of incorporating life skills into a handball training program on positive youth development. The Quasi-Experimental Design was employed as the study approach. A questionnaire was used to collect data for this study. The purposive sampling technique was used in this research. The sample of this study involved 40 young men aged 15-20 years divided into two groups, namely the handball training with life skill integration group (20 people) and the handball training without life skill integration group (20 people). The results of this research showed the significance value 0.000 0.05. The findings of this study revealed that the life skill development of the handball training group that integrated life skills in the program (Group A) was higher than the life skill development of the handball training group that did not receive life skill integration in the program (Group B). The development of adolescent life skills can be utilized in their daily lives, so that they can use the skills to address their life needs and obstacles.